Natural polymers in diabetes management: formulation prospects of Hibiscus rosa-sinensis mucilage for metformin sustained release - Kizza, Nsibambi Ronald; Bukke, Sarad Pawar Naik; Yahaya, Ungo-Kore Hussain; Bot, Yakubu Sunday (Frontiers in Bioengineering and Biotechnology, 2026)
Diabetes mellitus (DM) is a long-term metabolic disorder distinguished by hyperglycemia with the limitation of severe complications unless treated effectively. Metformin is the first-line agent for treating diabetes type 2 but has the drawback of a short half-life, incomplete absorption and is associated with gastrointestinal side effects requiring multiple times a day dosing. Sustained release (SR) formulations have been explored for the delivery of metformin while prolonging plasma levels, decreasing the frequency of dosing and increasing adherence improve patient compliance and outcomes related to diabetes. Some natural polymers have attracted attention as excipients for SR systems because they are biocompatible, biodegradable, and cost-effective. Specifically, Hibiscus rosa-sinensis mucilage has shown potential to be clinically useful due to its functional properties such as a high swelling index, gel-forming ability, stabilization of a matrix and compatibility with synthetic polymers. The extraction of the mucilage from the leaves and flowers is convenient, environmentally friendly and produces a stable hydrophilic pH stable and non-toxic polymer suitable for pharmaceutical applications. The use of a mucilage matrix in tablet formulations as well as hydrogels, beads, and/or nanoparticle systems would facilitate controlled diffusion and/or erosion -based metformin release designed to achieve zero order or Higuchi release kinetics. Additionally, the polymer would have the added therapeutic benefit due to its antioxidant and antidiabetic properties. Challenges of using mucilage include batch variability, microbial stability and limited clinical/non-clinical scientific data that indicated the need for the development of standardization and evaluation of its use. Future work includes the development of polymer.